CUSTOMER RELATIONSHIP MANAGEMENT PRACTICES OF INDIAN PUBLIC AND PRIVATE SECTOR BANKS: AN EXPLORATORY STUDY - P S, Lalitha; Paidipati, Kiran Kumar; Kumar, Arvind (Indian Journal of Finance and Banking, 2021)
The contemporary study focused on the impact of CRM parameters to identify the influencing factors towards customer satisfaction and customer loyalty. A sample of 1200 respondents chosen from public sector (SBI and of Andhra bank) and private sector banks (ICICI and HDFC) using multi-stage random sampling technique through a structured questionnaire. The study employed various statistical tools such as Percentage Analysis for demographical information, bank variables, and the CRM parameters. Mean Ranks for ranking the items and Reliability Analysis applied for obtaining reliable variables in constructing the CRM parameters. Exploratory Factor Analysis (EFA) was performed to identify highly influenced factors of CRM practices to improve level of satisfaction and loyalty in public and private banks. The explored results enlighten directions to the banking sector to provide some operational implications such as proactive involvement from personnel, and customized outreach in engaging customers to reduce the negative word-of-mouth (WOM) and increase the productivity of banks positively. These significant CRM strategies will reduce the attrition rate and improves customer retention in future. JEL Classification Codes: G210, G410, O180, D100.